'What Works Centres' : An Overview of a Growing Network in Supporting Government and Potential Considerations for Northern Ireland.: An Overview of a Growing Network in Supporting Government and Potential Considerations for Northern Ireland. (2016) - Northern Ireland., Assembly., Public Finance Scrutiny Unit,
No abstract available